2007
DOI: 10.1016/j.aap.2006.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Models of perceived cycling risk and route acceptability

Abstract: Perceived cycling risk and route acceptability to potential users are obstacles to policy support for cycling and a better understanding of these issues will assist planners and decision makers. Two models of perceived risk, based on non-linear least squares, and a model of acceptability, based on the logit model, have been estimated for whole journeys based on responses from a sample of 144 commuters to video clips of routes and junctions.The risk models quantify the effect of motor traffic volumes, demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(107 citation statements)
references
References 13 publications
5
100
0
2
Order By: Relevance
“…Non-linearity is observed also with the vehicle traffic, and again as the traffic is expressed as vehicle × km and the parameter is significantly lower than 1, this non-linearity suggests that the crash rates diminish when vehicular traffic augments. This finding is not surprising, especially when considering that congestion has been generally related to lower crash rates because of the lower speeds and the consequent higher margins of error in recognizing a potential conflict (e.g., 16,18,23).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Non-linearity is observed also with the vehicle traffic, and again as the traffic is expressed as vehicle × km and the parameter is significantly lower than 1, this non-linearity suggests that the crash rates diminish when vehicular traffic augments. This finding is not surprising, especially when considering that congestion has been generally related to lower crash rates because of the lower speeds and the consequent higher margins of error in recognizing a potential conflict (e.g., 16,18,23).…”
Section: Discussionmentioning
confidence: 93%
“…While some evidence points in the direction of cycling offering advantages because of the physical activity that reduces the health risks inherent to a sedentary life (e.g., 9,10,11), other evidence points in the direction of cycling bringing along negative effects because of the exposure to traffic pollution and crash risk (e.g., 12,13,14). When considering that the crash risk on a bicycle is definitely higher than the one on a motorized vehicle (e.g., 15,16,17) and factoring that it is the most significant disincentive to cycling (e.g., 18,19,20), investigating the factors contributing to the risk of being involved in a crash while riding a bicycle assumes a fundamental role for urban and transport planners aiming to increase the appeal of their cities and regions to potential cyclists.…”
Section: Introductionmentioning
confidence: 99%
“…This may lead to self-limiting of exposure to risk by choosing off-road paths or traffic calmed routes when they are available 231 . Choice of route may also related to cycling experience with experienced cyclists being more concerned with journey time and length than separation from traffic by contrast to the least experienced and some evidence of this has been reported 232 .…”
Section: Sources and Collection Of Environmental Cycle Crash Risk Datamentioning
confidence: 99%
“…Research by Petritsch and Landis on bicycle LOS in Florida found that the presence or absence of a bicycle lane was the most commonly cited reason for giving a roadway a high or low score, respectively (12). In their analysis of perceived cycling risk and route acceptability, Parkin et al found that bicycle lanes could mitigate the perceived risk of bicycling near high amounts of auto traffic (13).…”
Section: Literature Reviewmentioning
confidence: 99%